Effectiveness and Safety of Off-label Dosing of Non–vitamin K Antagonist Anticoagulant for Atrial Fibrillation in Asian Patients - Lee, Kwang-No; Choi, Jong-Il; Boo, Ki Yung; Kim, Do Young; Kim, Yun Gi; Oh, Suk-Kyu; Baek, Yong-Soo; Lee, Dae In; Roh, Seung-Young; Shim, Jaemin; Kim, Jin Seok; Kim, Young-Hoon (Scientific reports, 2020)
Non–vitamin K antagonist anticoagulants (NOACs) have been used to prevent thromboembolism in patients with atrial fibrillation (AF) and shown favorable clinical outcomes compared with warfarin. However, off-label use of NOACs is frequent in practice, and its clinical results are inconsistent. Furthermore, the quality of anticoagulation available with warfarin is often suboptimal and even inaccurate in real-world data. We have therefore compared the effectiveness and safety of off-label use of NOACs with those of warfarin whose anticoagulant intensity was accurately estimated. We retrospectively analyzed data from 2,659 and 3,733 AF patients at a tertiary referral center who were prescribed warfarin and NOACs, respectively, between 2013 and 2018. NOACs were used at off-label doses in 27% of the NOAC patients. After adjusting for significant covariates, underdosed NOAC (off-label use of the reduced dose) was associated with a 2.5-times increased risk of thromboembolism compared with warfarin, and overdosed NOAC (off-label use of the standard dose) showed no significant difference in either thromboembolism or major bleeding compared with warfarin. Well-controlled warfarin (TTR ≥ 60%) reduced both thromboembolism and bleeding events. In conclusion, the effectiveness of NOACs was decreased by off-label use of the reduced dose.